2012
DOI: 10.1002/hpm.2147
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the unit costs of public hospitals and primary healthcare centers

Abstract: The findings have implications for policy and decision making in the health sector in Palestine concerning the cost of services provided by hospitals and PHCs. The availability of a standardized data set for cost assessment would greatly enhance and improve the quality of financial information as well as efficiency in the use of scarce resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 6 publications
2
21
0
Order By: Relevance
“…This is the first study that estimated the operating costs and unit costs of hospital services in a big public urban hospital in Jordan. In line with findings from the previous two hospital autonomy reports from Jordan in 2002 (As‐Sayaideh et al , ; Banks et al , ) and reports from a number of developing countries (Vander Plaetse et al , ; Saksena et al , ; Chatterjee et al , ; Younis et al , ),we found that 50% and 17% of the hospital expenditures were consumed by inpatient and outpatient care centres respectively.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is the first study that estimated the operating costs and unit costs of hospital services in a big public urban hospital in Jordan. In line with findings from the previous two hospital autonomy reports from Jordan in 2002 (As‐Sayaideh et al , ; Banks et al , ) and reports from a number of developing countries (Vander Plaetse et al , ; Saksena et al , ; Chatterjee et al , ; Younis et al , ),we found that 50% and 17% of the hospital expenditures were consumed by inpatient and outpatient care centres respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Allocation rules were based on the American Hospital Association recommendations; these were also adapted from similar studies (Roberts et al, 1999;As-Sayaideh et al, 2002;Banks et al, 2002;Conteh and Walker, 2004;Saksena et al, 2010;Chatterjee et al, 2013;Younis et al, 2013).…”
Section: Cost Categories and Allocation Rulesmentioning
confidence: 99%
See 2 more Smart Citations
“…Unit costs were defined as the cost of one unit of "output" including admission, inpatient days, outpatient visits, emergency visits and surgical operations (12,18,19). Unit costs per hospital output were estimated using standard average costing; top down approach (17,18,(20)(21)(22). Total health expenditures of a provider was divided by the total output produced to determine the unit costs above.…”
Section: Methodsmentioning
confidence: 99%